Climate Change, Intergenerational Justice and Development - Christoph Lumer (Intergenerational Justice Review)
The subject of this paper is distributive justice in relation to financing greenhouse gas abatement. After separating the various questions of distributive justice in climate change (first section) and isolating the financing issue (second section), the paper explores whether any effective moral norms resolving this question already exist. It is argued that such norms still have to be constructed. As a basis for the further discussion, a criterion for moral duties is proposed, progressive norm welfarism, which takes up the constructivist idea (third section). Ethical , intuitive, moral and political considerations finally converge into a proposal for ‘no harm to developing countries’ (fourth section).